2015
DOI: 10.1108/ijmf-03-2013-0033
|View full text |Cite
|
Sign up to set email alerts
|

Governance and the corporate life-cycle

Abstract: Purpose -The purpose of this paper is to examine whether corporate governance changes along the corporate life-cycle. Design/methodology/approach -In a sample of 205 firms from 21 emerging market countries and using a life-cycle proxy from the dividends literature, the authors use a governance-prediction model which examines whether corporate governance differs along the corporate life-cycle. Findings -Mature firms tend to practice better overall corporate governance. Discipline and independence improve as fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 50 publications
3
32
0
1
Order By: Relevance
“…They also don't have urgent needs in this phase as their main goal is to hold on their position in the market by maximizing firms' internal operation. [34] concludes that best corporate governance can be found in the mature stage of FLC. This again explains why firms don't get involved in aggressive tax planning in this stage.…”
Section: Advances In Economics Business and Management Research Volmentioning
confidence: 96%
“…They also don't have urgent needs in this phase as their main goal is to hold on their position in the market by maximizing firms' internal operation. [34] concludes that best corporate governance can be found in the mature stage of FLC. This again explains why firms don't get involved in aggressive tax planning in this stage.…”
Section: Advances In Economics Business and Management Research Volmentioning
confidence: 96%
“…Previous studies have shown it is the monitoring role as opposed to the strategic and resource roles of governance that is most relevant for mature firms (see Filatotchev et al, 2006;O'Connor and Byrne, 2015). Our findings suggest that it is the strategic and resource functions of corporate governance, which is the most prominent role of governance in immature firms, which matters most for firm value.…”
Section: Resultsmentioning
confidence: 53%
“…Recent work also suggests that firms alter their governance needs across their life-cycle (see Filatotchev et al, 2006;O'Connor and Byrne, 2015). Governance attributes change and serves different functions as firms evolve.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Less attention has been given to the effect of corporate governance and its relation to each elements of the product lifecycle (Filatotchev et al 2006;O'Connor & Byrne 2015). The corporate governance literature in the domain of governance to value has demonstrated a causal relation between corporate governance and the firm's value and risk.…”
Section: Prior Studies and Hypothesis Development Firm's Product Lifementioning
confidence: 99%